VECTORS OF NEUROMARKETING APPLICATION FOR OPTIMIZING B2B TARGETING IN DIGITAL MARKETING - BORYSOVA, Tetiana; PROTSYSHYN, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The analysis of scientific publications revealed an insufficiently studied application of neuromarketing technologies for optimizing the targeting of corporate clients. The aim of the article was to investigate the conceptual foundations and identify the key vectors of neuromarketing application to enhance targeting effectiveness in B2B marketing. The following methods were employed: comparative analysis; graphical method; modeling; systems approach; synthesis; generalization.The study yielded the following findings. First, the research demonstrates that the use of biometric data in digital marketing and related fields is accompanied by a range of ethical and legal risks, including violations of privacy and improper data management. Second, the delineation of strategic-ethical and analytical-operational groups for the application of neuromarketing in B2B communications allows for a systematic approach to the use of neurodata, where the first group ensures compliance with international and local regulations, and the second focuses on practically enhancing communication effectiveness through message personalization, content optimization, and consideration of cognitive biases of the target audience. Third, the study confirms that a comprehensive approach to data management significantly minimizes ethical and legal risks and provides a foundation for the safe and effective use of neuromarketing tools in the B2B sector. Fourth, the specificity of B2B communications-including long-term contracts, multi-level decision-making committees, and the need for evidence-based content-requires the integration of neuromarketing data into planning and forecasting processes. Fifth, the proposed authorial model of the interrelation between neuroindicators, marketing stimuli, and B2B client behavior demonstrates that the combination of physiological signals, behavioral metrics, and personalized marketing stimuli creates a closed feedback loop, allowing communication strategies to be adapted according to individual and group neuroprofiles, thereby increasing targeting efficiency, message personalization, and overall effectiveness of B2B campaigns.The results of the study made it possible to propose practical recommendations for integrating neuromarketing tools into B2B communications.
Keywords: Internet marketing; digital marketing; targeting; neuromarketing; B2B; social media marketing